Human Resource Training and Development Program Strategy in Service Companies - Mulyadi Setiyo; Meddy Nurpratama (Gema Wiralodra, 2025)
This study aims to analyze effective and integrated human resource training and development strategies in service companies. Service organizations, particularly in the microfinance sector, are highly dependent on the competencies, soft skills, and service orientation of their frontline employees. The research adopts a qualitative approach using a literature review method, examining theories and best practices related to human resource training and development from various credible sources. The primary focus of the study is to explore how training strategies contribute to enhancing employee competencies and capabilities to support organizational success by emphasizing the development of technical skills and soft skills, particularly sales and communication training, in alignment with the service demands of the company. In addition, the training strategies incorporate continuous evaluation and the adjustment of training content in response to business developments. These findings are consistent with human resource development theories that highlight the importance of adaptive training programs to ensure relevance and effectiveness.